Evaluation of maternal serum levels of cell adhesion molecules and endothelial inflammatory markers in normal pregnancy, gestational hypertension and pre-eclampsia - Gupta, Taru; Arora, Sarika; Kumar, Anil; Gupta, Nupur; Gupta, Sangeeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hypertensive disorders complicate 5 to 10% of all pregnancies. Despite the still unexplained pathogenesis, endothelial dysfunctions and inflammatory mediators are thought to be responsible for the pathogenesis gestational hypertension and pre-eclampsia. Aims and objective of the study was to determine the serum levels of cell adhesions molecules - VCAM-1 and ICAM-1 and endothelial inflammatory markers TNF-α and homocysteine in normal pregnancies, Gestational Hypertension and in Pre-eclampsia Methods: The cross-sectional study was carried out in Department of Obstetrics and Gynecology and Biochemistry, ESI-PGIMSR, New Delhi between October 2013-April 2015. 150 patients who gave informed written consent were enrolled and were divided equally in three groups of 50 each (normotensive, gestational hypertensive and pre-eclamptic patients). Three groups have been compared in terms of variables such as age, BMI, gestational age, systolic and diastolic blood pressure, platelet count, AST, ALT, mode of delivery, neonatal weight, VCAM-I, ICAM-I, homocysteine and TNF-alpha concentrations. Results: We found the higher concentrations of vascular cell adhesions molecules (VCAM-1 and ICAM-1) and inflammatory mediators (homocysteine and TNF α) in gestational hypertensive patients and in pre-eclamptic patients. Out of four markers, concentrations of ICAM-1 was found in largest proportions and it was also statistical significant. P value was <0.001. Though in our study concentration VCAM-1, homocysteine and TNF-α were also high in gestational hypertensive groups as compared with normotensive patients, but they were not statistical significant. Conclusions: We conclude that higher concentrations of vascular cell adhesions molecules and inflammatory mediators may be responsible for hypertensive disorders of pregnancy suggesting the role of endothelial dysfunction as a central pathogenic feature in development of preeclampsia.